فعالية استخدم وسائل لعبة الاحتكارية في تعليم المفردات - Khairani, Riska; Mahmudah, Umi; Maimun, Agus; Siregar, Husnatul Hamidiyyah (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
This research was conducted to determine the effectiveness of teaching vocabulary using Monopoly game methods. This research uses a quantitative approach. This research was conducted at Al Ansar School. The data sources in this research are the seventh grade Arabic language teacher and the seventh grade students. Data was collected through tests, interviews and documents. The sample was the seventh class, F, as the experimental class, and the seventh class, H, as the control class. This research obtained results in the form of steps in using Monopoly game methods. A factor of 10.479 > Table 2.059, so it can be concluded that there is a significant impact of proprietary media on students’ vocabulary learning. أجري هذا البحث لمعرفة مدى فعالية تعليم المفردات باستخدام وسائل لعبة الاحتكارية. يستخدم هذا البحث المنهج الكمي. تم إجراء هذا البحث في مدرسة الأنصار. مصادر البيانات في هذا البحث هي معلم اللغة العربية للصف السابع وطلاب الفصل السابع. تم جمع البيانات عن طريق الاختبارات والمقابلات والوثائق. وكانت العينة هي الفصل السابع F كالفصل التجريبي والفصل السابع H كالفصل الضابط. حصل هذا البحث على نتائج في شكل خطوات في استخدام وسائل لعبة الاحتكارية. سوبة قدرها 10.479> جدول ت 2.059، لذلك يمكن الاستنتاج أن هناك تأثير كبير للوسائط الاحتكارية على تعلم مفردات الطلاب.